The Essence of the Concept of Responsibility - Ķinēna, Kristīne (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Social responsibility is a concept used across many field, for example, business, economics, political science, social and human science, etc. In every country has been made development plan,which is related to citizen's social responsibility and envionmental front. Every human daily routine begins with a sense of obligation and resposibility and action. People do not understand their actions and behavior of the direct consequences on the environment, other people and to ourselves.Conversely, by understanding ourselves as social and natural part, you can expect a long term positive results in the formation of responsibility and joint resposibility.This article deals with the concept of accountability structure and its relationship to the social environment.